Análisis tributario de la implementación de una tasa de circulación vehicular en la Provincia del Guayas. Caso puente Guayaquil - Samborondón - Villagomez De Oliveira E Souza, Vivianny (2015)
This document is based on research that seeks to contextualize a tax analysis on the implementation of a rate of vehicular movement in the province of Guayas, specifically where the construction of a new bridge will be made, that is, on the Daule river which includes flyover on Samborondón Avenue, path, path bridge, flyover on Narcisa de Jesus Martillo Moran Avenue and viaduct onto José María Egas Avenue, linking the districts of Guayaquil and Samborondón. It aims to provide an option of financing public works through a fee. In this case the rate to be applied will materialize in a toll; thus the collection impact thereof, in order to verify whether or not efficient analyzed. It was used benchmark analyzes and studies of other road projects in Ecuador for the purpose of delineating the investigative document, where certain barriers to access to information is denoted. The main problems of the project of construction of the Guayaquil Bridge - Samborondón are focused on the initial dispute between the national government with the aforementioned councils, why the information is very limited, most however, has been used to establish the amount which should be funded the provisions of Resolution 019A-SG-ICM-2015 dated May 14, 2015, where the Autonomous Government Decentralized Municipal Canton Samborondón by Municipal Ordinance, a method of financing is established, taking into consideration that it has a referential cost of 83.501 million two hundred eighty five dollars 16/100 United States of America (USD $ 83'501.285.16), of which the Municipality of Guayaquil contribute a third of the value of the same, (USD $ 27'833.761.72); and the Municipality of Samborondón provide two thirds of the value of it, the sum of (USD $ 55'667,523.44). Quantitative and qualitative characteristics were evaluated between the mode of financing proposed by the Municipality of Samborondón, through a Special Contribution Improvement and proposed in this paper, through the implementation of a fee. With all that is exposed must be obtained the respective conclusions of the analyzes, which will lead to make the respective recommendations.